Exploring and expanding supererogatory acts: beyond duty for a sustainable future - White, Gareth R. T. (Journal of business ethics, 2023)
Supererogation has gained attention as a means of explaining the voluntary behaviours of individuals and organizations that are done for the benefit of others and which go above what is required of legislation and what may be expected by society. Whilst the emerging literature has made some significant headway in exploring supererogation as an ethical lens for the study of business there remain several important issues that require attention. These comprise, the lack of primary evidence upon which such examinations have been made, attention has been given to only singular pro-social acts of organizations, and the focus has been upon the actions of large organizations. Furthermore, Heyd’s (Supererogation, Cambridge University Press, 1982) original taxonomy of six supererogatory acts, comprising Moral Heroism, Beneficence, Volunteering, Favour, Forgiveness and Forbearance, has been considered to be complete and other forms of supererogatory acts have not yet been explored. In order to address these gaps this study poses the research questions: First, it studies how a single, contemporary SME performs multiple supererogatory acts in its attempts to address its social and environmental goals that go beyond CSR. Second, it seeks to gain a deeper theoretical understanding of Heyd’s (Supererogation, Cambridge University Press, 1982) taxonomy of six forms of supererogation through the capture of primary data. This research makes a three-year case study examination of a single SME that has been formally recognized for its work in addressing social and environmental issues at local, national and global levels. Primary data are acquired of the supererogatory acts that it performs through a three-year participant observation case study, utilizing 61 interviews and 3 focus groups with internal and external stakeholders. In doing so, it addresses the empirical limitations of the extant research, substantiates each of the forms that supererogatory acts may take, and makes a contribution to the theory of supererogation by identifying a further class of act that is ‘Sharing’.